Right extended hepatectomy for hilar cholangiocarcinoma: A case report - Dahal, Romi; Adhikari, Krishna Mohan; Pradhan, Sumita; Bhandari, Ramesh Singh (Journal of Kathmandu Medical College, 2020)
Radical resection in a case of hilar cholangiocarcinoma is the only curative option. However resection in a hilar cholangiocarcinoma is a challenging procedure because of the low resectability rate. Only a few cases of hilar cholangiocarcinoma are operable because of the advanced nature of disease at presentation. Furthermore, the extent of surgery makes it a complicated process to attempt. We recently had a patient who underwent an open extended right hepatectomy and hepaticojejunostomy for a type IIIa hilar cholangiocarcinoma.The tumor was 20 mm in diameter and was located between the right hepatic duct and common hepatic duct. Radiological examination showed that the hepatic artery was not involved but the right portal vein was invaded by the tumor. CT volumetry was done and the future liver remnant was only 20% in the jaundiced patient. Preoperative drainage was done with percutaneous transhepatic biliary drainage from the left side. Portal vein embolization was done to augment future liver remnant to 30%.The patient underwent an extended right hepatectomy (right trisectionectomy combined with caudate lobectomy). The operation time was nearly 300 min, and the intraoperative blood loss was about 500 ml. However, in the postoperative period, the patient developed post hepatic liver failure which was managed successfully with conservative treatment. The postoperative hospital stay was 23 days.The final diagnosis was hilar cholangiocarcinoma with no nodal metastasis (pT2bN0M0) stage II (American Joint Committee on Cancer, AJCC).